Molecular Approaches to the Treatment, Prophylaxis, and Diagnosis of Alzheimer's Disease: Tangle Formation, Amyloid-β, and Microglia in Alzheimer's Disease - Kazuyuki Takata; Yoshihisa Kitamura (Elsevier, 2012)
Pathological hallmarks of Alzheimer's disease (AD) include senile plaques, neurofibrillary tangles (NFTs), synaptic loss, and neurodegeneration. Senile plaques are composed of amyloid-β (Aβ) and are surrounded by microglia, a primary immune effector cell in the central nervous system. NFTs are formed by the intraneuronal accumulation of hyperphosphorylated tau, and progressive synaptic and neuronal losses closely correlate with cognitive deficits in AD. Studies on responsible genes of familial AD and temporal patterns of pathological changes in brains of patients with Down's syndrome (Trisomy 21), who invariably develop neuropathology of AD, have suggested that Aβ accumulation is a primary event that influences other AD pathologies. Although details of the interaction between AD pathologies remain unclear, experimental evidences to discuss this issue have been accumulated. In this paper, we review and discuss recent findings that link the AD pathologies to each other. Further studies on the interaction between pathologies induced in AD brain may contribute to provide deep insight into the pathogenesis of AD and to develop novel therapeutic, prophylactic, and early diagnostic strategies for AD. Keywords:: amyloid-β, tau, actin, microglia, interaction, Alzheimer's disease